Food Security and Safety: Africans Perspectives A Review - , Emmanuel Chijioke Onwujekwe; , Constance Chinyere Ezemba (Archives of Current Research International, 2021)
The challenges of hunger in Africa, caused by food insecurity can only be mitigated by enhanced food security and food safety measures. Food safety has a significant role in ensuring food security. A primary cause of food insecurity is the decline in global food productivity. It is also a problem of poverty which has impacted adversely on the socio-economic life of its citizens. Africa is endowed with land resource that if transformed towards agricultural productivity has the capacity to ensure food security and sustainability. Agriculture, of which 85-90 per cent is rain-fed in sub-Saharan Africa, accounts for 35 percent of the region’s gross national product (GNP), 40 percent of exports and 70 percent of employment. Africa needs to leverage on agricultural innovation so as to boost its regional food output. It is essential that production and provision of safe food be given the attention it deserves by addressing the numerous challenges facing it so as to stimulate economic growth and ensure food security and safety in the African continent.